Preventable gynecological surgeries in hysterectomized women : a review of causes and measures of prevention - Anant, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hysterectomy, the most common gynaecologic surgery performed around the world. however, repeat gynaecologic intervention / surgery may be required for some conditions, adding cost and morbidity for patients and posing a burden on healthcare systems. The objective of the present study was to find out the incidence of and types of surgical intervention required post hysterectomy. Methods: A retrospective analysis of hospital records was done for gynecologic operative procedures done in post hysterectomy patients 2014-2016. Results: Out of a total of 1028 in the year 2014-2016 in our centre, 75 (7.3%) surgeries were performed for benign conditions in hysterectomized women. Hydrosalpinx(29%) was most common condition for surgery, followed by endometriosis(24%) with 31-40 years age group women undergoing the maximum surgeries. Vault prolapse(16%) in elderly and vaginal vault granulation(16%) in younger women also underwent a repeat gynecological procedure post hysterectomy. Conclusions: Some measures can be taken during the primary surgery(hysterectomy) to prevent a repeat gynaecological surgery in these women. Concurrent salpingectomy can prevent benign and malignant fallopian tube lesions and ovarian cancer . Endometriosis surgery should be precise to prevent any remnant ovarian or endometriotic foci. McCall’s culdoplasty in primary hysterectomy is proven to prevent vaginal vault prolapse. Most genitourinary fistulas can be prevented by detailed knowledge of pelvic anatomy, preoperative risk stratification of patients at higher risk of ureteric and urinary bladder injuries, meticulous surgical technique and judicious use of electrosurgical energy. Prevention is always better than a repeat surgery.